Defining Our Experience: A Psychosocial Analysis of the Racial, Gendered and Subjectivity of Black Women Employees in the British Prison Service - Thomas, Marcia Veronica (2016)
Prison occupation literature portrays an axiomatic image of the white male prison officer, which has a significant impact on mainstream society’ s perception of the people who work in prisons. This image of the prison employee inadvertently renders black women ‘invisible’and places them on the margins of the organisation. This thesis takes a different approach to examining prison occupation by applying new and varied views of being black female prison employees, by combining intersectionality theory and organisational psychodynamics to explore the psychosocial experience of this group of staff. Their perspective as gendered and racialised subjects provides an insightful account of what it ‘feels’ like to be black, women, and employees in the British Prison Service. Intersectionality highlights the ways in which gender and race are socially constructed categories that interact and influence relational dynamics at the individual, group, and organisational level. Through the multiple, and sometimes complicated, intersections of race, gender, employee status and hierarchy, my analysis exposes organisational and interactional dimensions of power, privilege and oppression prevalent in participants’ narratives. An organisational psychodynamic framework was applied to delve beneath the surface of interpersonal relationships and prison culture, to uncover the dynamic forces that block the free expression of gendered and racialised identity, and the acceptance and acknowledgment of difference. Twenty-four interviews were completed with seventeen participants, seven of whom were interviewed twice. All the participants worked for the British Prison Service. The black women in this study displayed a high level of awareness of their multiple identities and shared their experience, which illuminated how they negotiated the challenges they encountered as a result of their ‘outsider within’ position. The data from this research also revealed a cultural-historical and psychosocial characteristic defined as ‘Strong Black Woman’ that was consciously/unconsciously instigated to overcome adversity and challenges within this occupational space